Bilateral perinatal testicular torsion: successful salvage supports emergency surgery - Granger, Jeremy (BMJ Case Rep, 2016)
Perinatal testicular torsion (PTT) has poor rates of testicular salvage. Although rare, bilateral PTT carries the risk of anorchia. We present a case of a 2-day-old term infant with acute onset right-sided scrotal discolouration and tenderness. The infant was promptly taken to the operating theatre for emergency scrotal exploration. Bilateral extravaginal testicular torsion was identified, with the right testis appearing to have a more established ischaemic appearance compared to that on the left side. Intraoperative findings were representative of metachronous PTT with a short time period of only several hours separating the torsion events. Both testes were detorted and fixated in the scrotum. The infant made an uneventful recovery. Outpatient clinic review at 6 weeks and 6 months postoperatively confirmed no clinical evidence of testicular atrophy. Given the potential for contralateral torsion and the morbidity of anorchia, our experience supports the role for emergency scrotal exploration in suspected PTT.